HUBUNGAN INTERDIALITYC WEIGHT GAIN (IDWG) DENGAN KUALITAS HIDUP PASIEN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISIS: LITERATURE REVIEW - Zilfanny Sera Engla; Bayhakki Bayhakki; Oswati Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Chronic Kidney Disease (CKD) is one of the most serious diseases in the world with increasing prevalence from year to year. Hemodialysis is one of therapy forms for people with CKD. The problem that often occurs in hemodialysis patients is the increase in body weight between dialysis times which can cause symptoms that disturb the patient, so it can affect patient's life quality. This study aims to analyze research articles on the correlation between IDWG and life quality of CKD patients undergoing hemodialysis. This study uses literature review method. Data sources of published article search are conducted on google scholar, science direct and pubmed. The results of the study were based on 6 articles, the majority of respondents' ages were ≥ 45 years old (85,5%), most respondents (52,86%) had average IDWG percentage (4-6%), and the results of life quality assessment showed that the articles using WHOQOL-BREF the majority of patients' life quality was moderate, whereas articles using SF-36 the majority of patients' life quality was poor. Based on the 6 articles that have been reviewed, the results showed that (66,6%), which consists of 4 articles stated that there was a correlation between IDWG and life quality of CKD patients undergoing hemodialysis and 2 other articles stated there was no correlationKeywords: Hemodialysis, interdialityc weight gain, quality of lif